2019
DOI: 10.1097/md.0000000000016104
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the mandarin version of the tinnitus primary function questionnaire

Abstract: Tinnitus is a prevalent condition among different populations. As the nature of tinnitus is subjective, self-reported measures have been validated and utilized to assess psychometric properties of tinnitus patients. Without exception, Chinese clinicians have administered these measures to patients in mainland China after cross-cultural adaptation. However, shortcomings of these Mandarin measures limited the widespread use of them. Measures which can be fully adapted to the context of Chinese tinnitus patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 48 publications
4
11
0
5
Order By: Relevance
“…Statistically significant difference between groups divided by tinnitus handicap score was not found when it comes to level of frequency and intensity of tinnitus. The score of the THI is consistent with the reports of other authors who used the same questionnaire to evaluate the burden of patients with tinnitus [19,20]. In relation to the control group by the results of THI test, which coincides with the reports of other authors, we concluded that very severe and severe tinnitus reduce working ability, disrupt sleep, cause emotional disorders and significantly affect the quality of life in general [20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Statistically significant difference between groups divided by tinnitus handicap score was not found when it comes to level of frequency and intensity of tinnitus. The score of the THI is consistent with the reports of other authors who used the same questionnaire to evaluate the burden of patients with tinnitus [19,20]. In relation to the control group by the results of THI test, which coincides with the reports of other authors, we concluded that very severe and severe tinnitus reduce working ability, disrupt sleep, cause emotional disorders and significantly affect the quality of life in general [20].…”
Section: Discussionsupporting
confidence: 90%
“…The score of the THI is consistent with the reports of other authors who used the same questionnaire to evaluate the burden of patients with tinnitus [19,20]. In relation to the control group by the results of THI test, which coincides with the reports of other authors, we concluded that very severe and severe tinnitus reduce working ability, disrupt sleep, cause emotional disorders and significantly affect the quality of life in general [20]. In the group with tinnitus according to the results of BAI, the largest number of subjects had borderline anxiety, 28.8%, moderate anxiety was found in 23.3% of subjects, mild anxiety was found in 17.8%, severe anxiety 6.8% and 3 subjects had extreme anxiety or 4.1%.…”
Section: Discussionsupporting
confidence: 87%
“…A tradução desse mesmo instrumento para o idioma coreano, por exemplo, apresentou ICC semelhante ao encontrado na presente pesquisa (entre 0,50 e 0,82, nas sentenças) (Shin et al, 2019). A tradução da versão reduzida do questionário para o mandarim também mostrou ICC semelhante, com a ressalva que o aspecto emocional apresentou ICC˂0,70 (0,86 concentração; 0,61 emocional; 0,89 audição; 0,76 sono; e 0,85 no escore total) (Lu et al, 2019). O achado de Lu et al (2019) (Nahad et al, 2014;Kuk et al, 1990).…”
Section: Validação Do Questionário Tpfq Por Validade De Critériounclassified
“…Entretanto, vale enfatizar que a consistência interna adequada do THQ se relaciona com a análise de todos os itens, quando se analisa individualmente os fatores; o Fator 3 não pode ser considerado consistente e reprodutível (Kuk et al, 1990). Em estudos de tradução e validação para outros idiomas, foram encontrados valores de ⍺=0,82 a ⍺=0,95 para o TPFQ, conforme a Tabela 7 (Xin et al, 2021;Lu et al, 2019;Talaat et al, 2019;Shin et al, 2019;Tyler et al, 2014); e para o questionário THQ valores de ⍺=0,88 a ⍺=0,96, conforme a Tabela 8. Terwee et al, 2007).…”
Section: Validação Do Questionário Tpfq Por Validade De Critériounclassified
See 1 more Smart Citation